Forty years without mental hospitals in Italy - Barbui, Corrado (2019)
In 1978 Italy implemented Law Number 180, the reform law that blocked all new admissions to public mental hospitals. After 40years without mental hospitals, we aim at understanding the consequences of the Italian reform in terms of mental health care facility and staff availability. We compared the organization of the Italian mental health system with that of countries belonging to the Group of 7 (G7) major advanced economies. Italy has nearly 8 psychiatrists, 20 nurses, 2 social workers and less than 3 psychologists per 100,000 population, while for example in France there were 22 psychiatrists, in Japan 102 nurses, in the United States 18 social workers, and in Canada and France more than 45 psychologists per 100,000 population. In terms of inpatient facilities, no beds in mental hospitals were available in Italy, while in the other G7 countries mental hospital beds ranged from 8 in the United Kingdom to 204 in Japan per 100 000 population. In Italy there were fewer beds for acute care in general hospitals but more beds in community residential facilities than in the other G7 countries. Service use data showed variability in the provision of mental health care throughout the country. Soon after the implementation of the Italian reform the absolute number of compulsory admissions progressively declined, from more than 20,000 in 1978 to less than 9000 in 2015. Alongside the progressive decline of psychiatric beds imposed by Law 180, the age-adjusted suicide rate remained stable, ranging from 7.1/100,000 population in 1978 to 6.3/100,000 population in 2012. The population of psychiatric patients placed in Italian forensic psychiatric hospitals progressively declined. During the last 40years without mental hospitals, Italy has seen a progressive consolidation of a community-based system of mental health care. We highlighted, however, reasons for concern, including a decreasing staffing level, a potential use of community residential facilities as long-stay residential services, a still too high variability in service provision across the country, and lack of national data on physical restraints. At a national level, the resources allocated to mental health care are lower in Italy than in other high-income countries.